2022
DOI: 10.1371/journal.pone.0279692
|View full text |Cite
|
Sign up to set email alerts
|

HIV, sexual violence, and termination of pregnancy among adolescent and adult female sex workers in Malawi: A respondent-driven sampling study

Abstract: Female Sex Workers (FSWs) are a hard-to-reach and understudied population, especially those who begin selling sex at a young age. In one of the most economically disadvantaged regions in Malawi, a large population of women is engaged in sex work surrounding predominantly male work sites and transport routes. A cross-sectional study in February and April 2019 in Nsanje district used respondent driven sampling (RDS) to recruit women ≥13 years who had sexual intercourse (with someone other than their main partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The studies that were included reported qualitative and quantitative data on the experiences of adolescent mothers affected by HIV from sub-Saharan African countries: 12 studies from South Africa [4,11,12,13,15,22,23,24,25,26,29,32], 2 from Malawi [17,21], 1 from Zimbabwe [16], 6 Kenyan studies [18,20,27,31,33,34] (n=6), 1 from Lesotho [28] 1 from Uganda [19], and 2 multi-country studies [14, 30].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies that were included reported qualitative and quantitative data on the experiences of adolescent mothers affected by HIV from sub-Saharan African countries: 12 studies from South Africa [4,11,12,13,15,22,23,24,25,26,29,32], 2 from Malawi [17,21], 1 from Zimbabwe [16], 6 Kenyan studies [18,20,27,31,33,34] (n=6), 1 from Lesotho [28] 1 from Uganda [19], and 2 multi-country studies [14, 30].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies reported on quantitative data [4,11,12,14,15,17,18,19,20,22,24,26,28,29,31,32,33,34], five reported qualitative data [13,21,25,27,30], and one study used mixed methods [16]. The total number of participants included is 178,227, and the age range is between 12-18 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations